2022
DOI: 10.1093/sleep/zsac152
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a multisensor smart ring to evaluate sleep: in-lab and home-based evaluation of generalized and personalized algorithms

Abstract: Study Objectives Wearable sleep technology has rapidly expanded across the consumer market due to advances in technology and increased interest in personalized sleep assessment to improve health and mental performance. We tested the performance of a novel device, the Happy Ring, alongside other commercial wearables (Actiwatch 2, Fitbit Charge 4, Whoop 3.0, Oura Ring V2), against in-lab polysomnography (PSG) and at-home electroencephalography (EEG)-derived sleep monitoring device, the Dreem 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Previous research has repeatedly shown discrepancies between measures of subjective and objective sleep [ 31–34 ], suggesting that objective and subjective sleep outcomes may reflect different aspects of sleep. On the other hand, we cannot exclude that performance limitations of the ŌURA ring [ 35 ] may have affected the results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has repeatedly shown discrepancies between measures of subjective and objective sleep [ 31–34 ], suggesting that objective and subjective sleep outcomes may reflect different aspects of sleep. On the other hand, we cannot exclude that performance limitations of the ŌURA ring [ 35 ] may have affected the results.…”
Section: Discussionmentioning
confidence: 99%
“…Where manual and automatic detection were assessed separately, result ranges were displayed, and the absolute error was converted to percentage by dividing by the PSG measurements (Miller et al, 2021). Where only figures and no numbers were provided, calculations of mean absolute error were not possible (Grandner et al, 2023). The classification of bias for heart rate (HR) and HRV measures was done according to the following criteria proposed by Miller et al 2022): 0.0–0.1, trivial; 0.1–0.3, small; 0.3–0.5, moderate; 0.5–0.7, large; 0.7–0.9, very large; 0.9–1.0, nearly perfect (C. Bellenger et al, 2021; Hopkins et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, both WHOOP manual and automatic two and four sleep categorization could provide a practical alternative to PSG and perform well against other commercially available devices (Miller et al, 2021). Grandner et al showed moderate and comparable sleep specificity with commercially available activity trackers and that personalized algorithms that adapt to user data over time can improve device performance (Grandner et al, 2023).…”
Section: Accuracymentioning
confidence: 99%
“…In [43], the participants were asked to participate in one night in-lab PSG and two at-home EEG-monitoring sessions using the Dreem 2 Headband. Simulatnesously, the participants were asked to put on other wearable devices (rings or wristbands).…”
Section: Sleep Monitoring and Disordersmentioning
confidence: 99%
“…A Dreem headband (EEG-headband) was used in [39,57]. The Dreem 2 headband (EEG-headband) was used in [43]. The URGOnight device (an EEG headband) was used in [48].…”
Section: Mobile Device Charastristictsmentioning
confidence: 99%